Recent developments in the ISTTOK heavy ion beam diagnostic - Nedzelskiy, I.S.; Malaquias, A.; Henriques, R.B.; Sharma, R. (Вопросы атомной науки и техники, 2016)
The heavy ion beam diagnostic (HIBD) presents a powerful tool for investigations of hot plasmas in thermonuclear devices with magnetic confinement. When injected into the plasma, the primary probing beam of singly charged positive ions is ionized to a doubly charged state by impact with the plasma electrons and separated from the primaries due to the confining magnetic field of the plasma device. The resulting secondary ions are collected outside the plasma. The plasma parameters that can be measured by the HIBD are: the plasma electron density and temperature, and the electric and magnetic potentials. On the small tokamak ISTTOK (R = 0.46 m, a = 0.085 m, B = 0.5 T, Ip = 4…6 kA, = 5 × 10¹⁸ m ⁻³ , Te = 120 eV), the HIBD is based on a 20 keV Xe⁺ (or Cs⁺ ) beam injector and a multiple cell array detector (MCAD) collecting a fan of secondary Xe²⁺ (or Cs²⁺) ions emerging from the plasma along the primary beam trajectory. This paper describes the recent developments and improvements in the ISTTOK HIBD secondary beam detection. The capabilities of new detection system are illustrated by recent results of ISTTOK plasma MHD activity and electrode biasing studies. The on going developments of the multichannel multi-slit 90o cylindrical energy analyzer for the plasma potential and its fluctuations measurements and a novel approach of the HIBD use in real-time vertical plasma position control are also considered. Диагностика пучком тяжёлых ионов (ДПТИ) является мощным инструментом в исследованиях горячей плазмы в термоядерных установках с магнитным удержанием. Инжектируемый в плазму первичный пучок однозарядных положительных ионов ионизируется в двухзарядное состояние в столкновениях с электронами плазмы. В магнитном поле плазменной установки результирующие вторичные ионы отделяются от первичного пучка и детектируются вне плазмы. Измеряемые ДПТИ параметры плазмы включают плотность, температуру электронов, электрический и магнитный потенциалы. На малом токамаке ISTTOK (R = 0,46 м, а = 0,085 м, В = 0,5 Тл, Ip = 4…6 кА, = 5 × 10¹⁸ м ⁻³, Te = 120 эВ) ДПТИ состоит из 20 кэВ инжектора Xe ⁺ (или Cs⁺) пучка и мультиколлекторного детектора (МКД) вторичных Хе²⁺ (или Cs²⁺ионов, выходящих из плазмы вдоль траектории первичного пучка. Описываются изменения и улучшения детекторной системы ДПТИ на токамаке ISTTOK. Возможности новой детекторной системы иллюстрируются недавними результатами исследований МГД-активности и поляризации плазмы. Рассматриваются также разработка многоканального мультищелевого 90o цилиндрического анализатора энергии для измерений потенциала плазмы и его флуктуаций и новый подход использования ДПТИ для контроля вертикального положения плазмы в режиме реального времени. Діагностика пучком важких іонів (ДПВІ) є потужним інструментом у дослідженнях гарячої плазми в термоядерних установках з магнітним утриманням. Iнжектований в плазму первинний пучок однозарядних позитивних іонів іонізується в двозарядний стан у зіткненнях з електронами плазми. У магнітному полі плазмової установки результуючі вторинні іони відокремлюються від первинного пучка і фіксуються поза плазми. Вимірювані ДПВІ параметри плазми включають щільність, температуру електронів, електричний і магнітний потенціали. На малому токамацi ISTTOK (R = 0,46 м, а = 0,085 м, В = 0,5 Тл, Ip = 4…6 кА, = 5×10¹⁸ м ⁻³, Te = 120 еВ) ДПВІ складається з 20 кеВ інжектора Xe+ (або Cs+ ) пучка і мультиколекторного детектора (МКД) вторинних Хе²⁺ (або Cs²⁺) іонів, які виходять з плазми уздовж траєкторії первинного пучка. Описуються зміни і поліпшення детекторной системи ДПВІ на токамацi ISTTOK. Можливості нової детекторної системи ілюструються недавніми результатами досліджень МГД-активності і поляризації плазми. Розглядаються також розробка багатоканального мультищілинного 90o циліндричного аналізатора енергії для вимірювань потенціалу плазми та його флуктуацій і новий підхід використання ДПВІ для контролю вертикального положення плазми в режимі реального часу